2014
DOI: 10.3892/mmr.2014.2877
|View full text |Cite
|
Sign up to set email alerts
|

Association between the mitochondrial DNA 4977 common deletion in the hair shaft and hearing loss in presbycusis

Abstract: Abstract. The aim of the present study was to examine the role of the mitochondrial (mt) DNA common deletion (CD) 4977 (mtDNACD4977) in the hair shaft in patients with presbycusis. A total of 87 individuals with presbycusis and 95 normal-hearing controls were selected based on strict audiometric criteria. Nested polymerase chain reaction (PCR), sequencing and quantitative (q)PCR were used to examine the expression levels of mtDNA CD4977 in the hair shaft in presbycusis. Nested PCR of the hair shaft demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[28] A study by Hong Liu et al suggested a relationship between mtDNA 4977 bp deletion in the hair shaft and the severity of hearing loss in presbycusis. [17] These studies have therefore shown that mtDNA 4977 bp deletion is universally observed in patients with presbycusis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] A study by Hong Liu et al suggested a relationship between mtDNA 4977 bp deletion in the hair shaft and the severity of hearing loss in presbycusis. [17] These studies have therefore shown that mtDNA 4977 bp deletion is universally observed in patients with presbycusis.…”
Section: Discussionmentioning
confidence: 99%
“…Through extensive review of related data, this study eventually included 8 Chinese and foreign literature for meta-analysis. [17,27–32] The meta-analysis showed that the risk of mtDNA 4977 deletion in presbycusis increased (OR = 7.84, 95% CI: 3.63∼16.93). The OR values obtained after sensitivity analysis fluctuated between 4.57 and 10.63.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Markaryan et al25 described three extra big deletions of 5,354, 5,142, and 9,682 bp in the mitochondrial cytochrome c oxidase subunit III gene ( MT-CO3 ), in the structural element of the cochlea in patients with presbycusis. Further investigations revealed a significant relationship between the level of deletion and the severity of hearing loss in presbycusis 15,16. In addition to large deletions, point mutations in the mitochondrial genome have been determined as important factors in presbycusis 24,26.…”
Section: Discussionmentioning
confidence: 99%
“…The control region is composed of three hypervariable regions (HVR), HVR-I at 16,024−16,383, HVR-II at 57−372, and HVR-III at 438−574 (numbering according to NCBI Accession No NC_0122920.1) 13. A strong relationship between mtDNA coding region variation and presbycusis has also been reported in the literature;14–16 however, little is known about the relationship between variation in the mtDNA control region and the progression of presbycusis. Advances in the understanding of the intracellular mechanisms underlying presbycusis could lead to the development of diagnostic markers and therapies to slow or reverse the adverse changes in the auditory system characteristic of this disorder.…”
Section: Introductionmentioning
confidence: 91%